دور التمويل الأصغر في تقليل حدة الفقر والبطالة دراسة مصرف الادخار والتنمية الاجتماعية ولاية الخرطوم خلال الفترة (2008م- 2019م). - د. الشاذلي عيسى حمد عبد الله; أ.د. سعد عبد الله الكرم; عامر سعد الدين عثمان عبد القادر (White Nile Journal for Studies and Research, 2022)
This paper aimed the micro financial role which it given from the Sudanese Saving bank & Social Developmentin decreasing the poverty contour and unemployment in Khartoum state. The paper problems consist of relation between the micro financial and percentage of unemployment in Khartoum numerous questions such as: If there any statically relation between micro financial which it given from Sudanese Saving bank & Social Developmentto decreasing the poverty contour in Khartoum state and what the statically state. If there is any relation between the micro financial schemes successes which it related with given processing efforts from Sudanese Saving bank & Social Development- Khartoum. This Paper hypoes and supposing there is statically relating relation between micro financials which it given from Sudanese Saving bank & Social Development to decreasing the poverty in Khartoum state, and there is relation related with Sudanese Saving bank & Social Development efforts for micro financials to decreasing percentage unemployment, and there is relation between successions micro financial schemes and processing efforts which is given from Sudanese Saving bank & Social Development- Khartoum state. This scientifically paper depended and followed the description method and statically methods (SPSS) and the method of this study depending to gathering numerous of data reality which it related with this paper and then gathering many data by using the questionnaire and analyzed by SPSS programs. Meanwhile this paper explaining the results which it related with micro financial efforts from Sudanese Saving bank & Social Development while contributing and helping to decreasing the poverty status and decreasing the unemployment and it extending to offer working chances in schemes and economic activities which it rise up the per capita moreover to rise up the economic and social family level. And most of micro financial beneficiaries from Sudanese Saving bank & Social Development with different economics sectors which if financing the poverty slices and small producing from the youngness. The bank clearly aiming to developing the women sectors This paper recommending to increasing specialize financials schemes into different parts (Stats) in country and stringing strongly financial centers to easing for applying the affording micro financials and grantee the costing to the poor persons to occupied their economic activities to lead them out of poverty line special women and speared out the awareness and culturing of micro financial and saving between the aimed parts